Antigen-presenting cells containing multiple costimulatory molecules promote activation and expansion of antigen-specific memory CD8(+) T cells - Yang, Sixun (2008)
We have previously demonstrated that multiple immunizations with vector-based vaccines containing transgenes for tumor Ags and a triad of costimulatory molecules (TRICOM) enhance the expansion and functional avidity of Ag-specific memory CD8(+) T cells in a mouse model. However, the effect of enhanced costimulation on human memory CD8(+) T cells is still unclear. The study reported here was an in vitro investigation of the proliferation and function of CEA-specific human memory CD8(+) T cells following enhanced costimulation. Our results demonstrated that TRICOM costimulation enhanced production of multiple cytokines and expansion of CEA-specific memory CD8(+) T cells. The lytic capacity of memory CTLs toward CEA(+) tumors was also significantly enhanced. IL-2Rα (CD25) was upregulated dramatically following APC-TRICOM stimulation, suggesting that the enhanced expansion of memory CD8(+) T cells may be mediated by increased expression of IL-2R on memory T cells. The enhanced cytokine production and proliferation following TRICOM signaling was completely blocked by the combination of neutralizing Abs against B7-1, ICAM-1, and LFA-3, the costimulatory molecules comprising TRICOM. No difference in T-cell apoptosis was observed between APC-TRICOM and APC-wild-type groups, as determined by annexin V, Bcl-2, and active caspase-3 staining. Results indicated that enhanced costimulation greatly expanded human CEA-specific CD8(+) T cells and enhanced T-cell function, without inducing increased apoptosis of CEA-specific memory CD8(+) T cells.